10: Justice theories and the tourism workforce: a critical and empirical perspective - Fuchs, Matthias; Kronenberg, Kai (Edward Elgar Publishing, 2026)
In this chapter, we discuss justice-related challenges in the context of the tourism workforce. The most influential conception of justice in modern societies is based on Rawls’ work on the importance of distributive justice. Sen's capability approach, in contrast, emphasizes a person's individual capability to convert endowed resources into a decent life. From an epistemological perspective, we criticize contemporary justice theories by showing that they are grounded on untenable assumptions deduced from the rationality axiom. Instead, we propose a phenomenological and ethical reinterpretation of justice theories by emphasizing their relevance in legitimizing and empowering tourism-related institutions. While the literature mainly focuses on justice in the Global South, so-called advanced economies are likewise subject to socio-economic injustice in the form of income inequality, limited career opportunities and job-cutting developments. Findings from a mixed-methods study reveal job-related injustices for a large proportion of the tourism workforce of a major Swedish tourism region. We show how our plea for a transformative tourism science paradigm and an ‘institutional thickness’ approach may contribute to socio-economic justice for the tourism workforce. We highlight the role of tourism-related institutions, such as unions, destination development organizations and the regional administrative board.